Experimental Techniquetests Of Seismic- Resistant Rodspatial Structures - Isabekov Komolboy, (European Journal of Life Safety and Stability (2660-9630), 2022)
The article provides a methodology for the experimental investigation of small-scale crossstranded spatial structure (CSSS) models under dynamic loads such as seismic. Determination of the frequency and corresponding free and forced oscillations of the CSSS for different types of support and design schemes.